Tilapia lake virus: A structured phylogenetic approach - Abbadi, Miriam; Basso, Andrea; Biasini, Lorena; Quartesan, Rosita; Buratin, Alessandra; Davidovich, Nadav; Toffan, Anna (Frontiers in Genetics, 2023)
Tilapia Lake Virus (TiLV), also known as Tilapia tilapinevirus, is an emerging pathogen affecting both wild and farmed tilapia (Oreochromis spp.), which is considered one of the most important fish species for human consumption. Since its first report in Israel in 2014, TiLV has spread globally causing mortality rates up to 90%. Despite the huge socio-economic impact of this viral species, to date the scarce availability of TiLV complete sequences is severely affecting the knowledge on the origin, evolution and epidemiology of this virus. Herein, along with the identification, isolation and complete genome sequencing of two Israeli TiLVs deriving from outbreaks occurred in tilapia farms in Israel in 2018, we performed a bioinformatics multifactorial approach aiming to characterize each genetic segment before carrying out phylogenetic analysis. Results highlighted the suitability of using the concatenated ORFs 1, 3 and 5 in order to obtain the most reliable, fixed and fully supported tree topology. Finally, we also attempted to investigate the presence of potential reassortment events in all the studied isolates, and as a result, we report a reassortment event detected in segment 3 of isolate TiLV/Israel/939-9/2018 involved in the present study, and confirmed almost all the other events previously reported.